The Need of Global Social Nearness in Light of the Teachings of the Encyclical Fratelli Tutti. (10th November 2021) - Alva, Reginald
Abstract: Despite calls from global authorities to maintain social (physical) distance to stop the spread of COVID‐19, Pope Francis, in his encyclical Fratelli tutti, appealed for global social nearness to face the disastrous impact of the pandemic on people's lives. The encyclical raised several issues concerning the plight of the weak and the vulnerable amid the COVID‐19 pandemic. However, he did not address the plight of vulnerable people within the Catholic Church in the encyclical. Thus, in this paper, I will first examine the need for social nearness to weak and vulnerable people within the Catholic Church. Next, in light of the teachings of Fratelli tutti, I will examine the need for social nearness to the weakest in society, especially those affected by COVID‐19. Finally, I will examine the need for global mutual solidarity to face the various challenges caused by the pandemic. I will also explore the concrete proposals Pope Francis noted in his encyclical that are needed to accelerate global mutual solidarity during the pandemic and in the post–COVID‐19 world. The main source for this paper is Fratelli tutti itself. I will also refer to other church documents on social outreach and the opinions of experts in various fields.